Far field wake vortex evolution of two aircraft formation flight and implications on young contrails. (31st May 2020) - Unterstrasser, S.; Stephan, A.
Abstract: Large-eddy simulations (LES) have been employed to investigate the far-field four-vortex wake vortex evolution over 10min behind an aircraft formation. In formation flight scenarios, the wake vortex behaviour was found to be much more complex, chaotic and also diverse than in the classical single aircraft case, depending very sensitively on the formation geometry, i.e. the lateral and vertical offset of the two involved aircraft. Even though the case-by-case variability of the wake vortex behaviour across the various formation flight scenarios is large, the final plume dimensions after vortex dissolution are in general substantially different from those of single aircraft scenarios. The plumes are around 170 to 250m deep and 400m to 680m broad, whereas a single A350/B777 aircraft would produce a 480m deep and 330m broad plume. Formation flight plumes are thus not as deep, yet they are broader, as the vortices do not only propagate vertically but also in span-wise direction. Two different LES models have been employed independently and show consistent results suggesting the robustness of the findings. Notably, $CO_{2}$ emissions are only one contribution to the aviation climate impact among several others like contrails and emission of water vapour and nitrogen oxides, which would be all affected by the implementation of formation flight. Thus, we also highlight the differences in ice microphysical and geometrical properties of young formation flight contrails relative to the classical single aircraft case.